Hypnotic Automaticity in the Brain at Rest: An Arterial Spin Labelling Study. Issue 4 (2nd October 2019) - Rainville, Pierre; Streff, Anouk; Chen, Jen-I; Houzé, Bérengère; Desmarteaux, Carolane; Piché, Mathieu
Abstract: The feeling of automaticity reported by individuals undergoing a hypnotic procedure is an essential dimension of hypnosis phenomenology. In the present study, healthy participants rated their subjective experience of automaticity and resting-state arterial spin labelling (ASL) scans were acquired before and after a standard hypnotic induction (i.e., "neutral hypnosis"). The increase in perceived automaticity was positively associated with activity in the parietal operculum (PO) and seed-based coactivation analysis revealed additional associations in the anterior part of the supracallosal cingulate cortex (aMCC). This is consistent with the role of these regions in perceived self-agency and volition and demonstrates that these effects can be evidenced at rest, in the absence of overt motor challenges. Future studies should further examine if/how these changes in brain activity associated with automaticity might facilitate the responses to suggestions and contribute to clinical benefits of hypnosis.